Vibrational Spectroscopic Investigation of Tetracyanopalladate Bridged Two Dimensional Coordination Polymer Compounds of Pyrimidine - Akkaya, Yasemin; AKYÜZ, SEVİM; AKYÜZ, ZEKİ TANIL (Asian Journal Of Chemistry, 11/100 Rajendra Nagar, Sector 3, Sahibabad 201 005, Ghaziabad, India, 2013)
The two dimensional layered polymer compounds, M(PM)(2)Pd(CN)(4) {where M = Mn, Zn or Cd; PM = pyrimidine} have been prepared for the first time and their FT-IR (4000-400 cm(-1)) and Raman (4000-50 cm(-1)) spectra are reported. The compounds built up of [M(PM)(2)](2+) cations and square-planar [Pd(CN)(4)](2-) anions, which are linked by the bridging mu(2)-CN- groups. Pyrimidine was coordinated to M(II) through one of the nitrogen atom of its heterocyclic ring, as monodentate ligand. Vibrational assignments are given for the bands arising from the tetracyanopalladate layers and coordinated pyrimidine. The main bands of the vibrational spectra in the low frequency region were assigned to the stretching and deformational vibrations {nu(Pd-C), delta(PdCN), pi(PdCN), delta(CPdC)} originating from the host lattices.
Keywords: coordination compounds; IR and raman spectra; pyrimidine complexes; tetracyanopalladate antimicrobial activity; magnetic-properties; derivatives; FT-IR; complexes; schiff; bases; koordinasyon bileşikleri; pirimidin kompleksleri; tetrasyanopalladate antimikrobiyal aktivite; manyetik özellikler; türevler; kompleksler; bazlar